Characterization of zein-based core-shell microcapsules and matrix nanocapsules with encapsulated carvacrol - Spasojević, Ljiljana; Rajić, Danijela; Tošković, Dragan; Gojković Cvjetković, Vesna; Bučko, Sandra; Škrbić, Jelena; Fraj, Jadranka; Milinković Budinčić, Jelena; Petrović, Lidija; Katona, Jaroslav (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2026)
Composite micro- and nanocapsules made from natural proteins are increasingly used for various bioactive compound delivery applications due to their versatile nature and ability to carry a wide variety of therapeutic drug molecules. Capsules, both, core-shell and matrix types, have gained prominence in diverse sectors, from pharmaceuticals to food technology. Their widespread use is due to their encapsulation efficiency and controlled release properties. This study provides a physical-morphological characterization and a presentation of the preparation of particles derived from the corn protein-zein, with emphasis on core-shell and matrix configurations. Due to its strong antimicrobial effect against many different strains of bacteria and fungi, carvacrol was considered in this work. It was found that Pickering emulsions prepared as 10% O/W emulsion with 15% GA with the ratio Z:O=1:1.5 and the ratio Z:OSA starch=1:1 and 20 % of carvacrol on dry matter were the most suitable for the preparation of dry capsules. Analysis of matrix-type nanocapsules with 10% encapsulated carvacrol showed that the particles spherical in shape with a smooth surface and could be successfully dried and prepared in this formulation.